On the occurrence of the wreckfish Polyprion americanus in the Gulf of Trieste (northern Adriatic Sea) - Bettoso, Nicola (Array, 2020)
On 3rd June 2018 three juvenile specimens of Polyprion americanus were captured in the Gulf of Trieste. The wreckfish is a long-lived deep water demersal species characterized by an extended pelagic juvenile phase. The juvenile forms are recurrently recorded in the northern Adriatic and due to data deficiency for this species, original morphometric data are shown. The occurrence of P. americanus in the Gulf of Trieste is not a typical case of thermophilic species moving northward due to Mediterranean tropicalization, rather its recurrent appearance could be investigated for specific hydrological conditions coupled to its peculiar life span.